Nonlinear Servomotor in Single Pulse Simulation of Electrical Discharge Machining System Modeling - Hassan Lee; Azli Yahya; Nor Hisham Khamis; Shahrullail Samion (Institute of Advanced Engineering and Science, 2016)
Electrical Discharge Machining, EDM is a nonconventional and high precision machining. EDM system is considered a combination of servo system and EDM process. The servo system precisely controls the gap between electrode and workpiece for the continuous electrical discharges occurrence. Machining performance and stability depend on the performance of servo system. The EDM servo system usually modeled as a linear system, which ignores the nonlinearities of the motor. An assumption that the nonlinearities are insignificant in EDM system model may leads to modeling errors and result in poor control performance. In this study, nonlinear EDM servo system model was presented and the dynamic response of the model was analyzed and compared with the linear model. Simulation result shows a slightly difference in system response and a controller used in linear model is less efficient for a nonlinear EDM servo system model. The results are very useful for control strategy and can contribute to a better machining performance and stability of EDM applications.